Study of the realized absorptive capacity in the organizations of Colombia and Brazil - Elkin Perez; Ivan Dario Toro-Jaramillo (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The transformation and exploitation of knowledge are part of the absorptive capacity carried out. The article presents, from a linear regression model, the analysis of these two dimensions in 155 organizations in Brazil and 61 in Colombia. Design/methodology/approach: The methodology uses analysis of variance method and a linear regression model. The findings and Conclusions suggest the existence of a positive linear correlation between transformation and exploitation of external knowledge inside the studied organizations. Findings: The analysis of variance method and a linear regression model applied to a sample of 61 Colombian SMEs (Dane, 2012) and 155 SMEs of Brazilian ones (IBGE, 2011), results showed the existence of a positive linear correlation between the variables "transformation" and "exploitation" of knowledge, which shows interdependence between these two dimensions that make up the realized absorptive capacity. Practical implications: Research helps to show that if a high level of development of the capacity of knowledge transformation leads to a high level of organizational knowledge exploitation is verified. Originality/value: The empirical demonstration of the relationship between the dimensions that are part of the absorption capacity carried out, has been very little proven in the world. The research presents the first measurement that in organizations of Brazil and Colombia is carried out on the absorption capacity carried out.
Keywords: 650; Absorptive capacity; realized absorptive capacity; transformation; exploitation